Analisis Pengaruh Promosi dan Lokasi Terhadap Keputusan Menjadi Anggota Pada Gapoktan Mulya Jaya Unit LKMA Amanah Mandiri - Adhitya, Toni (Al-Muraqabah: Journal of Management and Sharia Business, 2023)
The purpose of this research is to find out how much influence promotion and location variables have on the decision to become a member of the Gapoktan Mulya Jaya Unit of LKMA "Amanah Mandiri". The method used is quantitative, the instrument in this research is a questionnaire given to respondents. As for the population in this research, there were 107 members who were active in financing and saving at the Gapoktan Mulya Jaya LKMA Unit "Amanah Mandiri" (respondents). The sampling technique used in this research is Non-Probability Sampling using a saturated sampling technique. The data was processed using descriptive data analysis, validity testing, classical assumption testing, and hypothesis testing. The results of the research found that the regression equation formed was Y = 9.932+ 0.299 X1 + 0.616 X2. If the promotion increases by one unit, the decision to become a member will increase by 0.299 and if the location increases by one unit, the decision to become a member will increase by 0.616. According to the results of the T test, it is known that the significant value of t is (0.000 < 0.05) with the result tcount = 6.160> t¬table = 1.65922, so H0 is rejected and Ha1 is accepted, which means there is a real (significant) influence on the Promotion variable (X1) on the Decision to Become a Member variable (Y). And it is known that the significant value of t (0.000 < 0.05) with the result tcount = 14,500> ttable = 1.65922, then H0 is rejected and Ha2 is accepted, which means there is a significant influence of the Location variable (X2) on the Decision to Become a Member variable (Y). Based on the R Square significance test that has been carried out. As a result, promotion and location have a significant influence on the decision to become a member by 0.841 or 84.1%. So the results obtained were that 84.1% of the decision to become a member was influenced by Promotion and Location variables, while the remaining 15.9% was influenced by other variables not examined in this research, such as price and product.